Education of elderly people on the example of students of the third age universities in Poland and Slovakia = Edukacja osób starszych na przykładzie studentów uniwersytetów trzeciego wieku w Polsce i Słowacji - Nowicka, Agnieszka; Kopinec, Pavol (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The increase in the number of advanced age people makes it necessary to pay more attention to the speci?c needs of the oldest generation, among which educational needs also play a signi?cant role. Education in late adulthood is a predictor of successful aging, a factor constituting the quality of life, as well as the best prevention and gerontological rehabilitation. Its general goal is to include older people in the education system including lifelong learning, understood as a multidimensional process that gives meaning to life against the backdrop of civilization, social and cultural changes.
Keywords: educational needs of elder people; University of the Third Age; educational programs for adults; potrzeby edukacyjne osób starszych; Uniwersytet Trzeciego Wieku; programy edukacyjne dla dorosłych